Diels–Alder adducts of a labdane diterpenoid from the Chinese liverwort Pallavicinia subciliata. Issue 7 (22nd February 2022) - Liu, Shu-Gong; Zhang, Chun-Yang; Zhou, Jin-Chuan; Han, Jing-Jing; Zhu, Ming-Zhu; Zhang, Jiao-Zhen; Li, Yi; Xu, Ze-Jun; Meng, Hui; Wang, Xue; Zong, Yan; Yuan, Shuang-Zhi; et al.
Abstract : A 7, 8- seco -2, 8-cyclolabdane diterpenoid, pallasubcin A (1 ), and three pallasubcin A-derived dimers, pallasubcins B–D (2–4 ), formed via a Diels–Alder reaction, were isolated from the Chinese liverwort Pallavicinia subciliata . Abstract : A 7, 8- seco -2, 8-cyclolabdane diterpenoid, pallasubcin A (1 ), and three rare pallasubcin A-derived dimers, pallasubcins B–D (2–4 ), formed via a Diels–Alder reaction between C-12–C-14′ and C-15–C-15′ were isolated from the Chinese liverwort Pallavicinia subciliata . Their structures were elucidated by comprehensive spectroscopic analysis, X-ray single crystal diffraction, and ECD calculations. Plausible biogenetic pathways are presented for all compounds. Preliminary anti-inflammatory determinations showed that compound 2 exhibited strong activity under nontoxic concentrations with a 73.03% (25 μ M) maximum inhibition rate of NO production on LPS-induced RAW 264.7 murine macrophages.